O significado e o sentido da escola pública para os jovens em conflito com a lei: uma discussão à luz da teoria da atividade de A. N. Leontiev - Pedroso, Ronaldo Revejes [UNESP] (2017)
The research looks for understanding the relationship between the school, its social significance and its meaning for young people in conflict with the law. It begins with a historical analysis of school institutionalization in Brazil and the creation of Youth and Adult Education (EJA) in order to understand the process of social construction and the meanings of the public schools in the country. From the experience of these young, the research looks for understanding what the school means to them. The goal is to identify how the relationship between the meaning and the sense of school interfere in the lives of students and how the absence of direction can cause difficulties for the educational work. The study has as methodological perspective the dialectical approach to comprehend the problematic through the categories that express the contradictory relations in reality. It proposes a better understanding of this youth in adult education and offers wide material for reflection, mainly to the professionals related to education. The field research was conducted at a public school in Araraquara / SP, where there is the target audience of this study. The place is the formation and coordination center for Young and Adult Education and offers basic education to students from various districts in town. The data indicate that the gap between the social significance of the school for teenagers may be cause of the conflict of them with the school. In this scenario, there is a disruption in the educational process and various conflicts arise among teenagers and the adult students. The study suggests possible and positive ways to overcome this problem at school.